Impact of Ownership Structure on Capital Structure of Listed Industrial Goods Companies in Nigeria - Salihu, Maimuna Adamu; Maigoshi, Zaharaddeen Salisu; Nasidi, Abubakar Dalladi (TSU-International Journal of Accounting and Finance, 2021)
This study examined the impact of ownership structure on capital structure using the data from the sampled industrial goods companies listed on the Nigerian Stock Exchange from 2014 to 2018. Regression analysis was run to determine the level of impact of ownership structure on capital structure. The analysis revealed that managerial, institutional and block holder ownerships have significant positive, negative and positive impact on capital structure. The findings of the study contribute to the agency theory and tradeoff theory by documenting that external monitoring mechanisms (debt providers) can be substituted with institutional investors. This indicates that highly geared firms can leverage their external financing need through seeking for institutional investors thereby, meeting their both financing and monitoring needs. In an organizational setting that presents an opportunity for insiders (managers or block holder owners) to expropriate the wealth of the firm at the expense of outsiders, the findings of the study show that debt financing can be used to minimize the agency costs. The study recommends that the management of the listed firms in the industry should balance a proper trade-off between debt and equity to reduce the risk of over burden external financing so as to increase the value of the firms for the benefit of equity holders.